Do shorter delays to care and mental health system renewal translate into better occupational outcome after mental disorder diagnosis in a cohort of Canadian military personnel who returned from an Afghanistan deployment? - David Boulos; Mark A Zamorski (BMJ Open)
Objective Mental disorders in military personnel result in high rates of attrition. Military organisations have strengthened their mental health systems and attempted to overcome barriers to care in order to see better outcomes. This study investigated the roles of mental health services renewal and delay to care in Canadian Armed Forces (CAF) personnel diagnosed with mental disorders.Design Administrative data were used to identify a retrospective cohort of 30 513 CAF personnel who deployed in support of the mission in Afghanistan. Study participants included 508 individuals with a mental disorder diagnosis identified from CAF medical records of a weighted, stratified random sample of 2014 individuals selected from the study cohort. Weighted Cox proportional hazards regression assessed the association of diagnosis era and delay to care with the outcome, after controlling for a broad range of potential confounders (eg, disorder severity, comorbidity). Taylor series linearisation methods and sample design weights were applied in generating descriptive and regression analysis statistics.Primary outcome The outcome was release from military service for medical reasons, assessed using administrative data for the 508 individuals with a mental disorder diagnosis.Results 17.5% (95% CI 16.0% to 19.0%) of the cohort had a mental disorder diagnosis after an Afghanistan-related deployment, of which 21.3% (95% CI 17.2% to 25.5%) had a medical release over a median follow-up of 3.5 years. Medical release risk was elevated for individuals diagnosed before 30 April 2008 relative to those with recent diagnoses (adjusted HR (aHR)=1.77 (95% CI 1.01 to 3.11)) and for individuals with a long delay to care (>21 months after return) relative to those with intermediate delays (8–21 months, aHR 2.47=(95% CI 1.28 to 4.76)).Conclusions Mental health services renewal in the CAF was associated with a better occupational outcome for those diagnosed with mental disorders. Longer delays to care were associated with a less favourable outcome.